On the Hydrogen Permeability and Adhesion of TiN/Ti Coatings Produced on Zr-1% Nb Alloy by Vacuum Ion-Plasma Methods; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 14, iss. 5 - Le Zhang; Nikitenkov N. N. Nikolai Nikolaevich; Sypchenko V. S. Vladimir Sergeevich; Korneva O. S. Olga Sergeevna; Kashkarov E. B. Egor Borisovich; Wang Yaoming (2020, 2020)
Title screen